Complete Blood Count Score Model Predicts Inferior Prognosis in Primary Central Nervous System Lymphoma - Feng, Yuhua; Liu, Yiping; Zhong, Meizuo; Wang, Leyuan (Frontiers in Oncology, 2021)
Background: Primary central nervous system lymphoma (PCNSL), an aggressive type of non-Hodgkin lymphoma, has a poor prognosis. Currently available prognostic scoring systems are inadequate. We therefore aimed to investigate the predictive values of complete blood counts (CBCs) in PCNSL. Materials and Methods: The cohort of this retrospective study comprised 73 PCNSL patients. The predictive values of selected CBCs, including neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), systemic immune inflammation index (SII), and systemic inflammation response index (SIRI), were analyzed. Results: Ages and Memorial Sloan Kettering Cancer Center (MSKCC) scores of PCNSL patients correlated with NLR, PLR, and SII values (p<0.05). Both age and MSKCC scores correlated with inferior progression-free survival (PFS) and overall survival (OS) (p<0.05). High NLR, PLR, SII, and SIRI were significant predictors of shorter PFS and OS(p<0.05). NLR, PLR, SII, and SIRI were integrated to generate a “CBC score” model that accurately stratified PCNSL patients into three risk groups. The median PFS for low-risk, intermediate-risk, and high-risk groups were 24 ((12.458-35.542), 17 (10.626-23.374), and 9 (8.893-19.107) months, respectively (p=0.011), and the median OS were 33(19.175-46.825), 18 (16.368-19.632), and 9 (6.521-11.479) months, respectively (p=0.008). Multivariate Cox regression model showed that MSKCC score (hazard ratio (HR)=3.791, p＜0.001), PLR (HR=1.003, p=0.013), and CBC score (HR=1.873, p=0.011) were independent predictors for PFS, whereas MSKCC score (HR=4.128, p＜0.001) , PLR (HR=1.003, p=0.005), and CBC score (HR=1.907, p=0.004) were independent predictors for OS. Conclusion: The CBC score model may be a promising predictive system for PCNSL patients.